Brain oximetry is not a good monitor on reducing neurological complications after cardiac surgery - Amouzegar Zavareh, Seyed Mohammadreza; Araghizade, Hasan; Eskandari, Nahid; Lak, Marzieh (Faculty of Medicine, Trisakti University, 2019)
BackgroundCerebral deoxygenation is related to several adverse systemic consequences. We aimed to assess the effect of noninvasive monitoring of cerebral oxygenation on reducing neurological complications after cardiac surgery.Methods In this randomized clinical trial, subjects were randomized into two groups: intervention group (111 subjects with monitoring of cerebral oximetry) and control group (112 subjects without any monitoring of cerebral oximetry). Monitoring of regional cerebral oxygen saturation (rScO2) was performed in the intervention group without any monitoring of cerebral oxygenation. The rScO2 was not recorded in the control group and no specific treatments were employed. Any neurological complications such as hallucinations, delirium, stroke, and length of stay in ICU after surgery were recorded. A p-value less than 0.05 was used as a cut-off for statistical significance.ResultsAfter surgery, in the intervention group one (1/111=0.09%) patient suffered from stroke and one patient had delirium, while in the control group three patients had stroke and three (3/112=2.6%) had delirium. There was no significant difference between the two groups regarding complications (p=0.527). The length of stay in ICU was 3.49 Â± 0.96 days in the case group and 3.40 Â± 0.80 days in the control group and there was no significant difference in the two groups (p=0.477).ConclusionMonitoring of rScO2 does not seem to be a good monitor for brain oxygenation. Further studies are needed to judge the usefulness of rScO2 for monitoring brain oxygenation.